The Association between Sleep-Disordered Breathing and Magnetic Resonance Imaging Findings in a Pediatric Cohort with Chiari 1 Malformation. Issue 1 (2015) - Amin, Reshma; Sayal, Priya; Sayal, Aarti; Massicote, Colin; Pham, Robin; Al-Saleh, Suhail; Drake, James; Narang, Indra
Abstract : BACKGROUND: The prevalence of sleep-disordered breathing (SDB) reported in the literature for Chiari malformation type 1 (CM1) is uniformly high (24% to 70%). In Canada, there is limited access to pediatric polysomnography (PSG). Therefore, the identification of clinical features would be invaluable for triaging these children. OBJECTIVE: To identify demographic features, clinical symptoms/signs and radiological findings associated with SDB in a large pediatric cohort with CM1. METHODS: A retrospective review was conducted on children with CM1 who underwent baseline PSG. Data were collected on patient demographics (age, sex, weight, height, body mass index), clinical symptoms (chart review and clinical questionnaires), diagnostic imaging of the brain and cervicothoracic spine, and medical history at the time of referral. RESULTS: A total of 68 children were included in the review. The mean (± SD) age of the children at the time of PSG was 7.33±4.01 years; 56% (n=38) were male. There was a 49% prevalence of SDB in this cohort based on the overall apnea-hypopnea index. Obstructive sleep apnea was the predominant type of SDB. Tonsillar herniation was significantly correlated with obstructive apnea-hypopnea index (r=0.24; P=0.036). CONCLUSIONS: A direct relationship between the degree of cerebellar tonsillar herniation and obstructive sleep apnea was demonstrated. However, further prospective studies that include neurophysiological assessment are needed to further translate the central nervous system imaging findings to predict the presence of SDB.